Strategi Pengembangan Desa Wisata Kampong Melayu Kota Pontianak (Development Strategy of Kampong Melayu Tourism Village in Pontianak City) - Ariffin, Muchammad; Pratiwi, Windi (STIE Malangkucecwara, 2025)
This study formulates a sustainable development strategy for Kampong Melayu Tourism Village, Sea Malay Continent, Pontianak, through SWOT analysis. This village has a distinctive cultural and natural tourism potential, but is constrained by minimal promotion and lack of a modern management system. The use of mixed methods in this study was by collecting data through observation, interviews, and questionnaire dissemination. The results showed the position of quadrant I (stable growth) with an internal score of 4.22 and external 4.28. The suggested strategies include the use of cultural and tourist attraction (SO) strengths, improving digital information and promotion systems (WO), strengthening branding and cooperation networks (ST), and developing creative marketing plans (WT). This finding is expected to be a reference for policymakers in designing competitive tourism village development